1996
DOI: 10.1161/01.cir.94.6.1316
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled, Randomized, Double-Blind Study of Intravenous Enalaprilat Efficacy and Safety in Acute Cardiogenic Pulmonary Edema

Abstract: Early administration of enalaprilat is effective and well tolerated in acute pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…49 One RCT only included responders to a previously given antihypertensive therapy. 50 Two out of 27 excluded trials involved a b-blocker arm and 18/27 excluded trials involved a calcium channel blocker arm. One excluded trial studied exclusively patients with acute aortic dissection.…”
Section: Resultsmentioning
confidence: 99%
“…49 One RCT only included responders to a previously given antihypertensive therapy. 50 Two out of 27 excluded trials involved a b-blocker arm and 18/27 excluded trials involved a calcium channel blocker arm. One excluded trial studied exclusively patients with acute aortic dissection.…”
Section: Resultsmentioning
confidence: 99%
“…High-dose enalaprilat lowers tissue perfusion pressure and negatively influences microcirculation, which may be important in the development of organ failure. Annane et al [11]showed that when MAP remains in the normal limits, enalaprilat has no influence on hemodynamics of internal carotid arteries and hepatosplanchnic arterial system, but it improves musculocutaneous and renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…en el edema pulmonar agudo, en comparació n con placebo. El enalaprilato produjo mayor reducció n de la presió n capilar pulmonar enclavada y mejora del flujo sanguíneo renal, pero se administró entre 6 y 18 h despué s de la llegada de los pacientes al SU, lo cual impide que estos datos sean ú tiles en el contexto de un tratamiento de emergencia 47 . En otro estudio sobre la eficacia de enalaprilato en pacientes con crisis hipertensivas en el SU, se evaluó su efecto en una cohorte pequeñ a de pacientes con ICA, y se demostró que no tenía efectos adversos graves y que el fá rmaco es ú til en el tratamiento de la ICA 48 .…”
Section: Inhibidores De La Enzima De Conversió N De La Angiotensinaunclassified